POTENTIAL OF PIPER CHABA FOR THE MANAGEMENT OF THE STORED-PRODUCT PEST (CALLOSOBRUCHUS CHINENSIS): POTENTIAL OF PIPER CHABA FOR THE MANAGEMENT OF THE STORED-PRODUCT PEST - ABHISHEK MUKHERJEE; ROHAN DAS; DEBOJOTI CHAKRABORTY (The Journal of Research ANGRAU, 2026)
The present study investigated the insect-repellent potential of Piper chaba (Piperaceae) stem in multiple formulations-dry powder, fume and water extract-against the pulse beetle Callosobruchus chinensis (Coleoptera: Bruchidae), a major pest of stored grains. With the increasing concern over pesticide resistance, toxicity to non-target organisms and residue hazards associated with synthetic insecticides, this research emphasises plant-based alternatives for sustainable pest management. Bioassays were conducted in I-tube (wind tunnel) to evaluate repellency using various concentrations of each formulation, and the results were statistically analysed using chi-square tests and regression analysis. The dry powder of P. chabastem showed a clear dose-dependent repellent response, with 1.75 g dry powder yielding 96.66% repellency ( ² = 29.36, p < 0.001). Similarly, the fume exhibited full repellency at higher release rates (2–4 ml/min) compared to 60% at 0.5 ml/min ( ² = 88.71, p < 0.001). Water extracts followed the same trend, with 100% extract achieving complete repellency and diluted forms showing reduced effectiveness ( ² = 66.25, p < 0.001). Phytochemical screening confirmed the presence of alkaloids, flavonoids, terpenoids, and phenols compounds previously associated with insecticidal activity. Infrared spectroscopy (IR) further validated the presence of functional groups such as O–H, C–H, and C=O, indicative of bioactive molecules. The findings establish P. chaba as a potent natural repellent with formulation-specific and concentration-dependent efficacy. Notably, the fume exhibits the highest repellency and richest phytochemical profile. This highlights P. chaba’s promise in eco-friendly pest control strategies, although further research is needed to assess toxicity on non-target species, residue safety, and field-level applicability.